Conditions Diagnosed on Bladder Biopsy in Adult Female Patients with Lower Urinary Tract Symptoms (LUTS) Refractory to Medical Treatment - Hafiz Abdul Rehman, Abeer Aftab Ahmad, Fahd Asif Sahi, Masroor Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The incidence of lower urinary tract symptoms (LUTS) as the sole presenting symptom for bladder cancer has traditionally been reported to be low. Refractory LUTS are a well-recognized initial presenting symptom in a small percentage of patients with newly diagnosed bladder cancer. Traditionally, patients who present with refractory LUTS are thought to have carcinoma in-situ (CIS) at diagnosis. Objectives: The objective of this study was to evaluate the evaluate the Conditions diagnosed on bladder biopsy in adult female patients with lower urinary tract symptoms (LUTS) refractory to medical treatment. Materials and Methods: We queried our database of bladder cancer patients in the hospital to identify patients who presented solely with LUTS and were subsequently diagnosed with bladder cancer. Demographic, clinical, and pathologic variables were examined. Results: 4.1% (14/340) of bladder cancer patients in our series presented solely with LUTS. Mean age and Charlson Co-morbidity Index of these patients was 66.4 years. Of the 14 patients in our data presenting with LUTS, 9 (64.3%), 4 (28.6%), and 1 (7.1%) patients presented with clinical stage Ta, carcinoma in Situ (CIS), and T2 disease. At a follow up of 6 months, recurrence occurred in 7 (50.0%) patients with progression occurring in 1 (7.1%) patient. 11 (78.6%) patients were alive and currently disease free, and 3 (21.4%) patients had died, with only one (7.1%) death attributable to bladder cancer. Practical implication: This study suggests that urologists should have a low threshold for evaluating patients with unexplained LUTS for underlying bladder cancer. Conclusions: It is concluded that incidence of LUTS as the sole presenting symptom in patients with newly diagnosed bladder cancer. Keywords: UTI, Bladder, Patients, Hyperplasia, LUTS, Cancer